Surfactant protein-D is an independent predictor of all-cause mortality in men with peripheral artery disease diagnosed by population-based screening - Christensen, Kimmie B.; Obel, Lasse M.; Lindholt, Jes S.; Sorensen, Grith L. (Frontiers in Cardiovascular Medicine, 2025)
IntroductionPeripheral artery disease (PAD) is a common condition caused by atherosclerosis, which leads to reduced blood flow to the limbs. PAD is associated with major adverse cardiovascular events (MACE) and major adverse limb events (MALE). Surfactant protein-D (SP-D) is a defense lectin expressed in the lungs and vasculature and has been previously associated with PAD.MethodsWe aimed to examine the prognostic value of plasma SP-D in relation to MACE, MALE, and all-cause mortality in 913 men with PAD diagnosed through population-based screening. The cohort was divided into low plasma SP-D (<420.4 ng/ml) and high SP-D (≥420.4 ng/ml) based on the 95th percentile of baseline measurements. The data were analyzed using univariate and multivariate Cox regression analyses.ResultsSP-D was not associated with MACE or MALE. All-cause mortality was significantly increased in the high SP-D group compared with the low SP-D group (31.1% vs. 14.9%, p = 0.003), with an adjusted hazard ratio of 2.40 (1.36–4.24), p = 0.003, over a mean follow-up period of 5.2 ± 1 years.DiscussionSP-D is not associated with MALE and MACE but is an independent predictor of all-cause mortality in men with PAD diagnosed through population-based screening.